Vocational High School Teachers’ Readiness to Implement the Deep Learning Approach in the Merdeka Curriculum: A Systematic Literature Review - Kaffa Serena Nur Hayati; Lugina Rizky Nugroho; Haeikal Ahmad Said; Hadromi; Ahmad Mustamil Khoiron (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The readiness of Vocational High School (SMK) teachers to implement the deep learning approach in the Merdeka Curriculum is analyzed through a systematic literature review. A total of 20 accredited national journal articles (2022–2026) sourced from Garuda, Google Scholar, and DOAJ were examined. The synthesis results reveal three main themes. First, teachers’ readiness is influenced by internal factors (self-efficacy, pedagogical competence, digital literacy, and emotional regulation) and external factors (learning environment, institutional support, industry partnerships, and professional learning communities). Second, strategies for implementing deep learning in vocational schools include project-based learning, teaching factory models, authentic assessment, integration of AI and coding, and social-emotional learning. Third, major challenges include limited teacher understanding, diverse student readiness, time constraints, inadequate digital infrastructure, and suboptimal process-based evaluation systems. Based on a comparison of strategies, hands-on training methods (75% practical activities) conducted over three days and combined with love-based education were found to be the most effective in improving teacher competence (+53.2 points). Strengthening continuous AI-based training, improving digital infrastructure, and developing teacher learning communities are recommended.